Carbachol-Induced Reduction in the Activity of Adult Male Zebra Finch RA Projection Neurons. (20th January 2016) - Meng, Wei; Wang, Song-Hua; Li, Dong-Feng
Abstract : Cholinergic mechanism is involved in motor behavior. In songbirds, the robust nucleus of the arcopallium (RA) is a song premotor nucleus in the pallium and receives cholinergic inputs from the basal forebrain. The activity of projection neurons in RA determines song motor behavior. Although many evidences suggest that cholinergic system is implicated in song production, the cholinergic modulation of RA is not clear until now. In the present study, the electrophysiological effects of carbachol, a nonselective cholinergic receptor agonist, were investigated on the RA projection neurons of adult male zebra finches through whole-cell patch-clamp techniques in vitro. Our results show that carbachol produced a significant decrease in the spontaneous and evoked action potential (AP) firing frequency of RA projection neurons, accompanying a hyperpolarization of the membrane potential, an increase in the evoked AP latency, afterhyperpolarization (AHP) peak amplitude, and AHP time to peak, and a decrease in the membrane input resistance, membrane time constant, and membrane capacitance. These results indicate that carbachol reduces the activity of RA projection neurons by hyperpolarizing the resting membrane potential and increasing the AHP and the membrane conductance, suggesting that the cholinergic modulation of RA may play an important role in song production.